Perspectives of Pregnant Women about Commitment of Obstetricians and Gynecologists to Informed Consent Principle Regarding Delivery Method, Isfahan, Iran - Ahmad Reza Zamani; Ziba Farajzadegan; Reza Sirous (مجله دانشکده پزشکی اصفهان, 2012)
Background: Natural vaginal delivery is usually considered as the best method of delivery. However, the rate of cesarean section has been increasing several times during recent decades. Nowadays, approximately 50-65% of deliveries in Iran are performed as cesarean section. This trend can be dealt with by providing correct information about the advantages and disadvantages of cesarean and vaginal delivery. The present study aimed to investigate the extent of information gynecologists provide to pregnant mothers about the advantages and disadvantages of various childbirth methods (informed consent factors). Methods: This cross-sectional, descriptive study was conducted on 482 pregnant women at the third trimester of pregnancy who had been admitted in obstetrics and gynecology ward of a certain number of private hospitals, university hospitals, non-academic public hospitals, and hospitals affiliated to Social Security Organization for delivery or any other reason. Pregnant mothers were selected though convenient non-randomized method. The informed consent questionnaire consisted of 30 questions about disadvantages, advantages, costs, alternative methods, and the method and quality of presenting information to mothers. The data was analyzed by chi-square, Kruskal-Wallis and Mann-Whitney tests in SPSS16. Findings: Mean total information presented to the pregnant women was 1.06 ± 0.93 out of 4. The presented information included complications of cesarean (0.82 ± 1.07), complications of natural vaginal delivery (0.85 ± 1.1), advantages of cesarean (1.29 ± 1.00), advantages of vaginal delivery (1.34 ± 1.00), costs (2.29 ± 1.30), and alternative deliveries (0.95 ± 1.10). Quality of information presentation was scored as 1.21 ± 1.14. Conclusion: The commitment of obstetricians and gynecologists to obtain informed consents from mothers was very low. In addition, it was associated with a particular bias in some cases. Thus, implementing developed and proper planning seems necessary to educate and promote awareness and knowledge of patients toward patient rights. On the other hand, the attention of physicians needs to be attracted toward concentrating more on patient rights.